Estimation of pre and postharvest losses of tropical fruits in Ethiopia. (16th December 2019) - Bantayehu, Muluken; Alemayehu, Melkamu; Abera, Mirkuz; Bizuayehu, Solomon
The research was conducted to quantify and identify major factors of fruit loss. Questionnaires were used to collect data from 180 randomly selected fruit producers of six districts. Descriptive statistics and multiple regression analysis were employed for data analysis. Result revealed that fruit losses in the preharvest and postharvest were 20.7% and 22.1% of the total production respectively. Multiple regression analysis depicted means of income, use of pesticides and use of compost and manure had significantly contributed to losses in the preharvest. Regression analysis revealed experience, educational level of producers and shortage of labour had significant effect for losses during harvesting whereas chemical treatment and educational level affected losses in storage. Moreover, experience, distance from market, educational level were significant factors of fruit loss during marketing. Therefore, the study suggests adoption of scientific approach, education, skill developments and use of pre and postharvest technologies are important to minimise losses.